Effect of mentorship program on mentees’ psychosocial development - Ismail, Azman; Abdullah, Nor’Ain; Ridzwan, Ahmad Azan; Wan Ibrahim, Wan Nur Ain; Ismail, Yusof (SciPress Ltd, 2015)
The study investigates the role of mentorship in enhancing mentees’ psychosocial development. It utilized self-administered questionnaires completed by undergraduate military students at a public higher learning institution in Malaysia. The outcomes of SmartPLS path model analysis revealed two important findings: firstly, communication insignificantly correlated with psychosocial development. Secondly, support significantly correlated with psychosocial development. The results confirm that communication does not act as an important determinant of mentees’ psychosocial development. However, support does act as an important psychosocial development in the studied organization. This paper also provides discussion, implications and conclusion.